Penerapan Metode Bernyanyi untuk Meningkatkan Kemampuan Bahasa Arab Anak Usia Dini - Nazhatu, Nazhatu; Mugniyah, Athifatil; Kurnia, Lita (E-JURNAL AKSIOMA AL-ASAS, 2024)
Arabic for early childhood sounds so difficult to learn because in essence early childhood is children aged 0-6 years. However, on the other hand, Arabic is very important for early childhood. Nowadays, many early childhood are taught Arabic with various methods, but there are interesting and less interesting methods to be given to early childhood. Arabic lessons are difficult lessons for them to understand because one of the reasons is using hijaiyah letters and pronunciation which is quite difficult. Therefore, in this study, an attempt will be made to apply the singing method to improve the Arabic language skills of early childhood in the Abu Bakar class aged 5-6 years at the Al-Qur'an La Tansa Education Park. This study uses the Classroom Action Research method which is carried out in 2 cycles, each cycle has 8 meetings in cycle 1 and 2 meetings in cycle 2. The stages in the classroom action research carried out by the researcher start from planning, implementation, observation and reflection. In this study, the researcher used several data collection techniques including observation, interviews and documentation. The results of the Classroom Action Research that has been implemented at the level of completion of the application of the singing method to improve the Arabic language skills of early childhood in cycle I are at a percentage of 67% (very good) and cycle II at a percentage of 70% (very good). Thus, the singing method can improve the Arabic language skills of early childhood in the Abu Bakar class of the Al-Qur'an La Tansa Education Park.. Keywords: Singing Method, Arabic, Early Childhood